Students' Motivation in English as a Medium of Instruction (EMI) for non-English Subject in an Islamic Higher Education - Agus Husein As Sabiq (Mathematics Education Study Program, 2025)
English as a Medium of Instruction (EMI) has become increasingly prevalent in non-English subjects within Islamic higher education institutions. However, students’ motivation to engage in EMI-based learning varies due to linguistic, cultural, and pedagogical factors. This study explores the motivation of students in an Islamic higher education institution where EMI is implemented in non-English subjects, examining the key factors that influence their attitudes, engagement, and academic performance. Using a mixed-method approach, data were collected through surveys and interviews with 5 lecturers and 128 students enrolled in EMI courses. The findings indicate that while many students perceive EMI as beneficial for improving their English proficiency and expanding global academic opportunities, challenges such as limited language proficiency, instructor effectiveness, and cultural adaptation impact their motivation. The study also reveals that students with strong intrinsic motivation tend to perform better in EMI courses, whereas those with extrinsic motivation often struggle due to linguistic barriers. Moreover, Islamic values and institutional support play a crucial role in shaping students' attitudes toward EMI. The study suggests that integrating language support programs, adaptive teaching strategies, and culturally responsive pedagogy can enhance students’ motivation and academic success in EMI-based learning. The implications of these findings are significant for policymakers and educators aiming to implement EMI effectively in Islamic higher education contexts.